A concept analysis of adolescent friendship. Issue 3 (25th February 2019) - Roach, Ashley
Abstract: Aim: The purpose of this study is to provide a definition of adolescent friendship to aid in nursing research and practice. Background: Friendships are an essential part of adolescence and can have significant impacts on health outcomes. Adolescent friendships are associated with decreased depression, suicidal ideation, anxiety, and improved self‐management of chronic conditions. However, the concept of friendship has not been well defined in the nursing literature, especially in the context of adolescents. Design: Walker and Avant's method of concept analysis was used as a framework for this analysis. Data Sources: Seventeen articles were reviewed, representing a variety of disciplines including child development, psychology, sociology, behavioral sciences, medicine, education, public health, and nutrition. Additional sources included online definitions of friendship. Review Methods: After reviewing the sources, the author identified attributes, antecedents, and consequences. Model case, a borderline case, and contrary case were developed and empirical referents identified. Results: The analysis resulted in a clear definition of adolescent friendship, containing the attributes of support, intimacy, affection, trust, ability to manage conflict, and time. Conclusions: Understanding the attributes, antecedents, and consequences of adolescent friendships will help nurses in assessing and supporting these influential relationships during this important development period.